Endocannabinoid Systetm: Neuropharmacological Implications - Vivek Kumar Sharma; Akshay Chandel; Gunad Acharya; Rahul Deshmukh (Medicine Science, 2016)
Marijuana or cannabis has been part of humanity's medicine chest for almost as long as history has been recorded. Cannabinoids are a class of diverse chemical compounds isolated from cannabis that act on cannabinoid receptors (CB1 & CB2). The ligands for these receptor proteins include the endocannabinoids (produced naturally in the body by humans and animals), the phytocannabinoids (found in cannabis and some other plants) and synthetic cannabinoids (manufactured artificially). The endogenous cannabinoid system, named after the plant that led to its discovery, is perhaps the most important physiologic system involved in establishing and maintaining human health. The human body's neurological, circulatory, endocrine, digestive and musculoskeletal systems have now all been shown to possess cannabinoid receptor sites. Indeed, even cartilage tissue has cannabinoid receptors, which makes cannabis a prime therapeutic agent to treat various complicated ailments. In each tissue, the cannabinoid system performs different tasks, but the goal is always the same: homeostasis, the maintenance of a stable internal environment despite fluctuations in the external environment. The endocannabinoid system, with its presence in almost all organs especially in CNS makes it a bridge between body and mind. By understanding this system we begin to see a mechanism that explains how states of consciousness can promote health and sense of well being. Nausea, vomiting, stimulation of appetite, symptomatic relief of cancer pain and/or management of neuropathic pain, stroke, cancer, drug dependence, glaucoma, autoimmune uveitis, osteoporosis, sepsis, hepatic, renal, intestinal and cardiovascular disorders are the various diverse areas where cannabinoids have shown their therapeutic presence and potential. In present work cannabinoids are presented as a viable therapeutic target in CNS disorders that include Alzheimer's disease, amyotrophic lateral sclerosis, multiple sclerosis, epilepsy, Parkinsons and Huntingtons disease. [Med-Science 2016; 5(2.000): 562-82]